Бізнес-планування в системі економічного управління підприємством - Ларка, Людмила Сергіївна; Нелюб, Катерина Петрівна (НТУ "ХПІ", 2016)
Запропоновано критерії оцінювання ефективності стратегій у маркетинговому розділі бізнес-плану. Метою статті є визначення основних підходів до складання бізнес-планів в залежності від мети економічного управління підприємством. Завданнями статті є обґрунтування провідної ролі управління маркетингом в системі управління підприємством, дослідження основних стандартів бізнес-планування. Було застосовано матричні методи стратегічного управління. Зроблено висновок про необхідність застосування маркетингових досліджень для інформаційного забезпечення маркетингового розділу бізнес-плану.

The elements of the enterprise management system are given. The tasks of function control subsystems are systematized. The leading role of marketing management in the enterprise management system is substantiates. The purpose of the article – the definition of the main approaches to the preparation of business plans, depending on the purpose of the economic management of the enterprise. The objectives of the article are to study the leading role of marketing management in the enterprise management system, the study of basic business planning standards. Matrix methods of strategic management have been applied. The basic standards of business planning are shown. The methodological tools for SWOT-analysis are given. The conclusion about the need to incorporate a set of strategic enterprises in the marketing section of the business plan is shown. The criteria of evaluation of efficiency pricing, sales, product and enterprise communication strategies are given. The role of marketing research in the information support of the marketing section of the business plan is shown.
Business planning in the system of economic management of the enterprise
Keywords: управління економічне; бізнес-планування; маркетинг; SWOT-аналіз; стратегія маркетингова; набір стратегічний; economic management; business planning; marketing; SWOT-analysis; marketing strategy; strategic set